Elite screening and nutritional profiling of Syzygium caryophyllatum (L.) Alston -an underutilized fruit tree. Issue 2 (3rd April 2023) - Chandra, Amitha S.; Siril, E.A.; Radhamany, P.M.
ABSTRACT: Syzygium caryophyllatum is an underutilized minor fruit tree that bears globular fruits. When they ripen, they turn a deep purple or black colour. Even though the fruits are edible, consumption is low due to the low proportion of edible parts and limited supply of fruits. In the present study, twenty collections of S. caryophyllatum from various parts of Kerala State, India, were evaluated based on morphological (qualitative and quantitative), and biochemical traits of fruits. The findings revealed a wide range of variation among the collections. Among the selected candidate plus trees (CPTs), one CPT, SC3, appeared as a distinct candidate from all other collections in the dendrogram based on quantitative and biochemical traits. The grouping pattern in cluster analysis results was supported by a scatter plot based on Principal coordinate Analysis (PCoA). Various fruit traits of SC3 showed superiority and thus this tree was selected as the most promising among 20 CPTs with maximum pulp percentage, pulp-to-seed ratio, TSS, anthocyanins, ascorbic acid, total sugar, and minimum seed percentage. The nutritional profiling of SC3 fruit showed a vital source of nutritious elements with antinutrient concentrations falling within the acceptable range.